Laminate, method for manufacturing same, and method for manufacturing semiconductor package

By forming an antistatic layer with uniform and excellent conductivity on the substrate surface of the fluororesin film, the problem of uneven antistatic function in the prior art is solved, and the excellent antistatic performance and uniform appearance of the laminated body are achieved.

CN119768274APending Publication Date: 2025-04-04AGC INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380061129.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The antistatic function required by the existing fluororesin film in three-dimensional packaging and other sealing processes is uneven, which affects the safety of electronic circuits.

Method used

A laminated body with a film-like substrate and an antistatic layer provided on the surface of the substrate is adopted. The surface energy of the antistatic layer is between 35 and 70 mN/m, the thickness deviation is less than 30%, and an antistatic agent that can be dispersed in water. The antistatic agent contains a conductive polymer and a conductive filler.

Benefits of technology

The uniformity and excellence of antistatic properties are achieved, the surface resistance value of the laminated body is reduced, the conductivity is improved, the electrostatic damage is avoided, and the appearance is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768274A_ABST
    Figure CN119768274A_ABST
Patent Text Reader

Abstract

This laminate is provided with a film-like base material and an antistatic layer provided on one surface of the base material, the surface energy of the surface of the base material in contact with the antistatic layer being 35-70 mN / m, and the thickness deviation of the antistatic layer being less than 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a laminate, a method for manufacturing the laminate, and a method for manufacturing a semiconductor package. This application claims priority from Japanese Tokugan Application No. 2022-139312 filed in Japan on September 1, 2022, and the contents of which are incorporated herein. Background Art

[0002] Fluororesin films have excellent mold release properties and can be used as process films for forming electronic components such as semiconductor sealing. On the other hand, fluororesin films are easily charged with static electricity, and care must be taken when contacting and peeling off electronic circuits. When fluororesin films are used not only for semiconductors but also for sealing processes such as SiP (System-in-Package) or three-dimensional packaging, there is a possibility that the electronic circuits being used may be damaged. Therefore, providing a fluororesin film with an antistatic function is very beneficial in industry. As a fluororesin film having an antistatic function, a film having an antistatic layer on one surface of a fluororesin substrate is known (Patent Documents 1 and 2). Prior art literature Patent Literature

[0003] Patent Document 1: International Publication No. 2016 / 093178 Patent Document 2: International Publication No. 2016 / 125796 Summary of the invention Technical problem to be solved by the invention

[0004] However, the antistatic function required in the sealing process such as the above-mentioned three-dimensional packaging may be required to have uniformity. According to the studies of the present inventors, the antistatic function of the fluororesin films having an antistatic function described in Patent Documents 1 and 2 is not uniform in some cases.

[0005] The present invention provides a laminate having excellent antistatic performance, a method for manufacturing the laminate, and a method for manufacturing a semiconductor package using the laminate. Solutions to technical problems

[0006] The present disclosure provides a stacked body having the following structures [1] to

[14] , a method for manufacturing the stacked body, and a method for manufacturing a semiconductor package. [1] A laminate comprising a film-like substrate and an antistatic layer provided on one surface of the substrate, wherein: The surface energy of the surface of the substrate in contact with the antistatic layer is 35 to 70 mN / m, The thickness deviation of the antistatic layer is less than 30%. [2] The laminate according to [1] above, wherein the antistatic layer contains an antistatic agent dispersible in water. [3] The laminate according to [2] above, wherein the antistatic agent comprises at least one selected from a conductive polymer and a conductive filler. [4] A laminate as described in any one of [1] to [3] above, wherein the substrate comprises at least one selected from fluororesin, polymethylpentene, syndiotactic polystyrene, polycyclic olefin, silicone rubber, polyester elastomer, polybutylene terephthalate, polyethylene terephthalate and polyamide. [5] The laminate according to [4] above, wherein the fluororesin comprises at least one selected from the group consisting of ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer. [6] The laminate according to any one of [1] to [5] above, wherein the surface of the substrate in contact with the antistatic layer is subjected to a corona treatment or a plasma treatment. [7] The laminate according to any one of [1] to [6], further comprising a release layer provided on the surface of the antistatic layer opposite to the substrate. [8] The laminate according to any one of [1] to [7] above, which is a release film used in a step of sealing a semiconductor element with a curable resin. [9] A method for producing a laminated body comprising coating an antistatic layer coating liquid on one surface of a film-like substrate to form an antistatic layer, wherein: The surface energy of the surface of the substrate coated with the antistatic layer coating liquid is 35 to 70 mN / m, The antistatic layer coating liquid comprises water, a water-miscible organic solvent and an antistatic agent dispersible in water, The content of water is 50.0 to 99.9% by mass relative to the total amount of the antistatic layer coating liquid. The content of the water-miscible organic solvent is 14.0 to 30.0% by mass relative to the total amount of the antistatic layer coating liquid. The surface tension of the antistatic layer coating liquid is below 34 mN / m.

[10] The production method according to [9] above, wherein the water-miscible organic solvent contains alcohol.

[11] The production method as described in

[10] above, wherein the alcohol comprises isopropanol.

[12] The production method described in any one of [9] to

[11] above, wherein before applying the antistatic layer coating liquid, the surface of the substrate to be coated with the antistatic layer coating liquid is subjected to a corona treatment or a plasma treatment.

[13] The manufacturing method as described in any one of [9] to

[12] above, further comprising: after forming the antistatic layer, forming a release layer on the surface of the antistatic layer opposite to the substrate.

[14] A method for manufacturing a semiconductor package, comprising: placing the laminate described in any one of [1] to [8] on the inner surface of a mold; placing a substrate having a semiconductor element fixed thereto in the mold having the stacked body arranged therein; Sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and The sealing body is demolded from the mold. Effects of the Invention

[0007] According to the present disclosure, it is possible to provide a laminate having excellent antistatic performance, a method for manufacturing the laminate, and a method for manufacturing a semiconductor package using the laminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 This is a schematic cross-sectional view showing one embodiment of the present laminate. Figure 2 This is a schematic cross-sectional view showing another embodiment of the present laminate. DETAILED DESCRIPTION

[0009] Hereinafter, the embodiments of the present disclosure are described in detail. However, the embodiments of the present disclosure are not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not necessarily required unless otherwise expressly stated. The same is true for numerical values ​​and their ranges, which do not limit the embodiments of the present disclosure.

[0010] In the present disclosure, the term "process" includes a process independent of other processes, and also includes a process if the purpose of the process can be achieved without being clearly distinguished from other processes. In the present disclosure, a numerical range expressed by "to" includes the numerical values ​​described before and after "to" as a minimum value and a maximum value, respectively. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical ranges recorded in the present disclosure, the upper limit or lower limit of its numerical range can also be replaced by the value shown in the embodiment. In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or total amount of the plurality of substances present in the composition, unless otherwise specified. In the present disclosure, when an embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the dimensions of the components in the drawings are schematic, and the relative relationship between the dimensions of the components is not limited thereto.

[0011] In the present disclosure, the "unit" of a polymer refers to a part derived from a monomer that exists in a polymer and constitutes the polymer. In addition, a structure obtained by chemically converting the structure of a certain unit into a polymer is also referred to as a unit. In addition, depending on the circumstances, the unit derived from each monomer is described by the name of the monomer plus the name of the "unit". In the present disclosure, films and sheets are collectively referred to as "films" regardless of their thickness. In the present disclosure, acrylate and methacrylate are collectively referred to as “(meth)acrylate”, acrylic acid and methacrylic acid are collectively referred to as “(meth)acrylic acid”, and (meth)acryloyl and methacryloyl are collectively referred to as “(meth)acryloyl”. In the present disclosure, a (meth)acrylic polymer is a polymer containing a unit based on a monomer having a (meth)acryloyl group or (meth)acrylic acid. Hereinafter, a monomer having a (meth)acryloyl group or (meth)acrylic acid is also referred to as a "(meth)acrylic monomer".

[0012] [Laminated body] A laminate according to one embodiment of the present disclosure (hereinafter also referred to as a "laminate") is a laminate having a film-like substrate and an antistatic layer arranged on one surface of the substrate, wherein the surface energy of the surface of the substrate in contact with the antistatic layer is 35 to 70 mN / m, and the thickness deviation of the antistatic layer is less than 30%.

[0013] The present laminate was found to be excellent in antistatic performance. According to the inventor's research, the antistatic layer of this laminate has a high conductivity per unit thickness and excellent conductivity compared to the case where the thickness deviation of the antistatic layer is more than 30%. Due to the excellent conductivity of the antistatic layer, the surface resistance value of the laminate can be reduced, showing excellent antistatic performance. As the reason for the high conductivity per unit thickness of the antistatic layer, it is believed that the antistatic layer is formed with a uniform thickness and the distribution and orientation of the antistatic agent become uniform to form a uniform conductive path. Furthermore, since the thickness variation of the antistatic layer is less than 30%, color unevenness due to uneven thickness of the antistatic layer can be suppressed, and the appearance is excellent.

[0014] The present laminate has only to include a substrate and an antistatic layer, and other structures are not particularly limited. Figure 1 This is a schematic cross-sectional view showing one embodiment of the present laminate. Figure 1 The laminated body 1 shown includes a substrate 2 and an antistatic layer 3 in this order. Figure 2 This is a schematic cross-sectional view showing another embodiment of the present laminate. Figure 2 The laminate 1 shown in the figure has a substrate 2, an antistatic layer 3 and a release layer 4 in sequence. When the laminate 1 is used for sealing a semiconductor element, the substrate 2 is arranged in contact with a mold, and after resin sealing, the antistatic layer 3 or the release layer 4 is in contact with the sealing body (i.e., a semiconductor package body in which the semiconductor element is sealed). In addition to the substrate 2, the antistatic layer 3 and the release layer 4, the laminate 1 may also have other layers. Hereinafter, each component of the present laminate will be described in detail.

[0015] (Base material) The material of the substrate is not particularly limited. The substrate generally contains a resin, and examples of the resin include fluororesins, polymethylpentene, syndiotactic polystyrene, polycyclic olefins, silicone rubber, polyester elastomers, polybutylene terephthalate, polyethylene terephthalate, and polyamide. In one embodiment, from the viewpoint of excellent demoulding property of this laminate, the substrate preferably includes a resin with demoulding property (hereinafter also referred to as "demolding resin"). Demolding resin refers to a resin with demoulding property in which the layer composed of the resin has demoulding property. As demoulding resin, fluororesin, polymethylpentene, syndiotactic polystyrene, polycyclic olefin, silicone rubber, polyester elastomer, polybutylene terephthalate and polyamide etc. can be cited. From the viewpoint of excellent demoulding property, heat resistance, strength and elongation at high temperature, fluororesin, polymethylpentene, syndiotactic polystyrene and polycyclic olefin are preferred, and from the viewpoint of excellent demoulding property, fluororesin is more preferred. The resin contained in the substrate may be one or more than one. The substrate is particularly preferably composed of only fluororesin alone. However, even when the substrate is composed of only fluororesin alone, it is also possible to include resins other than fluororesin within the scope of not damaging the effect of the invention.

[0016] As the fluororesin, a fluoroolefin polymer is preferred from the viewpoint of excellent mold release properties and heat resistance. A fluoroolefin polymer is a polymer having a unit based on a fluoroolefin. A fluoroolefin polymer may also have other units in addition to the unit based on a fluoroolefin. Examples of the fluoroolefin include tetrafluoroethylene (hereinafter referred to as "TFE"), vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoropropylene (hereinafter referred to as "HFP"), and chlorotrifluoroethylene. The fluoroolefin may be used alone or in combination of two or more.

[0017] As the fluoroolefin polymer, ethylene-TFE copolymer (hereinafter also referred to as "ETFE"), TFE-HFP copolymer (hereinafter also referred to as "FEP"), TFE-perfluoro (alkyl vinyl ether) copolymer and TFE-HFP-vinylidene fluoride copolymer etc. can be cited. From the viewpoint of mechanical properties, it is preferably selected from at least one of ETFE and FEP. Fluoroolefin polymer can be used alone or in combination of two or more.

[0018] As the fluoroolefin polymer, ETFE is preferred from the viewpoint of high elongation at high temperature. ETFE is a copolymer containing a unit derived from TFE (hereinafter also referred to as a "TFE" unit) and a unit derived from ethylene (hereinafter also referred to as an "E unit"). As ETFE, a polymer having TFE units, E units, and units based on a third monomer other than TFE and ethylene is preferred. The crystallinity of ETFE can be easily adjusted by the type and content of the units based on the third monomer, thereby easily adjusting the storage modulus or other tensile properties of the substrate. For example, ETFE has a tendency to improve tensile strength and elongation at high temperatures (especially around 180° C.) by having units based on a third monomer (especially a fluorine-containing monomer).

[0019] As the third monomer, there may be mentioned a monomer containing a fluorine atom and a monomer not containing a fluorine atom. As the fluorine atom-containing monomer, the following monomers a1 to a5 may be mentioned. Monomer a1: Fluorinated olefins having 2 or 3 carbon atoms. Monomer a2: X(CF2) n Fluorinated alkylethylenes represented by CY=CH2 (wherein X and Y are each independently a hydrogen atom or a fluorine atom, and n is an integer of 2 to 8). Monomer a3: fluorovinyl ethers. Monomer a4: fluorovinyl ethers containing functional groups. Monomer a5: a fluorine-containing monomer having an aliphatic ring structure.

[0020] Specific examples of the monomer a1 include fluoroethylenes (eg, trifluoroethylene, vinylidene fluoride, vinyl fluoride, chlorotrifluoroethylene, etc.) and fluoropropylenes (eg, hexafluoropropylene (HFP), 2-hydropentafluoropropylene, etc.).

[0021] As the monomer a2, a monomer in which n is 2 to 6 is preferred, and a monomer in which n is 2 to 4 is more preferred. In addition, a monomer in which X is a fluorine atom and Y is a hydrogen atom, that is, a (perfluoroalkyl)ethylene is preferred. Specific examples of the monomer a2 include the following compounds. CF3CF2CH=CH2, CF3CF2CF2CF2CH=CH2((perfluorobutyl)ethylene (hereinafter also referred to as "PFBE")), CF3CF2CF2CF2CF=CH2、 CF2HCF2CF2CF=CH2, CF2HCF2CF2CF2CF=CH2.

[0022] Specific examples of the monomer a3 include the following compounds. Among the following compounds, the monomer which is a diene is a cyclopolymerizable monomer. CF2=CFOCF3, CF2=CFOCF2CF3、 CF2=CF(CF2)2CF3(perfluoro(propyl vinyl ether) (hereinafter also referred to as "PPVE")), CF2=CFOCF2CF(CF3)O(CF2)2CF3, CF2=CFO(CF2)3O(CF2)2CF3、 CF2=CFO(CF2CF(CF3)O)2(CF2)2CF3, CF2=CFOCF2CF(CF3)O(CF2)2CF3, CF2=CFOCF2CF=CF2, CF2=CFO(CF2)2CF=CF2.

[0023] Specific examples of the monomer a4 include the following compounds. CF2=CFO(CF2)3CO2CH3、 CF2=CFOCF2CF(CF3)O(CF2)3CO2CH3, CF2=CFOCF2CF(CF3)O(CF2)2SO2F.

[0024] Specific examples of the monomer a5 include perfluoro(2,2-dimethyl-1,3-dioxole), 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxole, and perfluoro(2-methylene-4-methyl-1,3-dioxolane).

[0025] As the monomer not containing a fluorine atom, the following monomers b1 to b4 may be mentioned. Monomer b1: olefins. Monomer b2: vinyl esters. Monomer b3: vinyl ethers. Monomer b4: unsaturated acid anhydride.

[0026] Specific examples of the monomer b1 include propylene and isobutylene. As a specific example of the monomer b2, vinyl acetate may be mentioned. Specific examples of the monomer b3 include ethyl vinyl ether, butyl vinyl ether, cyclohexyl vinyl ether and hydroxybutyl vinyl ether. Specific examples of the monomer b4 include maleic anhydride, itaconic anhydride, citraconic anhydride and 5-norbornene-2,3-dicarboxylic anhydride.

[0027] The third monomer may be used alone or in combination of two or more. As the third monomer, monomer a2, HFP, PPVE and vinyl acetate are preferred from the viewpoint of easy adjustment of crystallinity and excellent tensile strength at high temperature (particularly around 180° C.), HFP, PPVE, CF3CF2CH=CH2 and PFBE are more preferred, and PFBE is particularly preferred. That is, as ETFE, a copolymer having a TFE unit, an E unit and a unit based on PFBE (hereinafter also referred to as a “PFBE unit”) is particularly preferred.

[0028] In ETFE, the molar ratio of TFE unit to E unit (TFE unit / E unit) is preferably 80 / 20 to 40 / 60, more preferably 70 / 30 to 45 / 55, and further preferably 65 / 35 to 50 / 50. When TFE unit / E unit is within the above range, ETFE has excellent heat resistance and mechanical strength.

[0029] The ratio of the units based on the third monomer in ETFE to the total of all units constituting ETFE (100 mol%) is preferably 0.01 to 20 mol%, more preferably 0.10 to 15 mol%, and further preferably 0.20 to 10 mol%. If the ratio of the units based on the third monomer is within the above range, ETFE has excellent heat resistance and mechanical strength.

[0030] When the units based on the third monomer include PFBE units, the ratio of the PFBE units to the total of all units constituting ETFE (100 mol%) is preferably 0.5 to 4.0 mol%, more preferably 0.7 to 3.6 mol%, and further preferably 1.0 to 3.6 mol%. When the ratio of the PFBE units is within the above range, the tensile strength of the film at high temperatures, particularly at about 180° C., is improved.

[0031] The substrate may be formed only of resin or may contain other components in addition to the resin. Other components include lubricants, antioxidants, antistatic agents, plasticizers, and mold release agents. From the perspective of not easily contaminating the mold, the substrate preferably does not contain other components.

[0032] The thickness of the substrate is preferably 6 to 500 μm, more preferably 25 to 300 μm, and further preferably 25 to 150 μm. If the thickness of the substrate is below the upper limit of the above range, the laminate can be easily deformed and has excellent mold compliance. If the thickness of the substrate is above the lower limit of the above range, the laminate is easy to handle, such as roll-to-roll operation, and wrinkles are not easily generated when the laminate is stretched while being arranged to cover the mold cavity of the mold. The thickness of the substrate is measured in accordance with ISO 4591:1992 (B1 method of JIS K7130:1999: a method for measuring thickness of a sample collected from a plastic film or a plastic sheet by a mass method).

[0033] The surface of the substrate may have a surface roughness. The arithmetic mean roughness Ra of the surface of the substrate is preferably 0.2 to 3.0 μm, more preferably 0.5 to 2.5 μm. If the arithmetic mean roughness Ra of the surface of the substrate is above the lower limit of the above range, the demolding property from the mold is better. If the arithmetic mean roughness Ra of the surface of the substrate is below the upper limit of the above range, it is difficult for the laminate to form perforations. The arithmetic mean roughness Ra was measured in accordance with JIS B 0601: 2013 (ISO 4287: 1997, Amd. 1: 2009). The reference length lr (cutoff value λc) for the roughness curve was set to 0.8 mm.

[0034] The substrate may be unstretched or stretched. For example, unstretched polyamide film, biaxially stretched polyamide film, biaxially stretched PET (polyethylene terephthalate) film, biaxially stretched PEN (polyethylene terephthalate) film, biaxially stretched syndiotactic polystyrene film and unstretched PBT (polybutylene terephthalate) film are commercially available. In addition, polyimide film, polyphenylene sulfide resin film and cross-linked polyethylene film etc. can also be used.

[0035] The surface of the substrate may be subjected to any surface treatment, and examples of the surface treatment include corona treatment, plasma treatment, flame treatment, UV ozone treatment, silane coupling agent coating, and adhesive coating. The surface of the substrate in contact with the antistatic layer is preferably hydrophilized from the viewpoint of making its surface energy more than 35mN / m. As hydrophilized, as long as the surface energy of the treated surface is reduced, for example, corona treatment, plasma treatment, flame treatment, UV ozone treatment can be exemplified. Wherein, from the viewpoint of the ease of introduction of the simplicity of the device and the industrial process, preferably corona treatment or plasma treatment. If corona treatment or plasma treatment is implemented, hydrophilic functional groups will be generated on the surface, and the surface energy will decrease.

[0036] The substrate may be a single layer or a multilayer structure. As a multilayer structure, a structure in which each layer includes a plurality of layers of resin is stacked. In this case, the resins contained in each of the plurality of layers may be the same or different. From the viewpoints of mold compliance, tensile elongation, and manufacturing cost, the substrate is preferably a single layer. From the viewpoint of laminate strength, the substrate preferably has a multilayer structure. The multilayer structure can be, for example, a structure in which the layer comprising the above-mentioned release resin (preferably fluororesin) is stacked with a resin film (can be a film containing only resin) comprising a resin such as polyester, polybutylene terephthalate, polystyrene (preferably syndiotactic) or polycarbonate, or a structure in which the layer comprising the first release resin, the above-mentioned resin film and the layer comprising the second release resin are stacked in sequence. The layer comprising the release resin and the resin film can be stacked via an adhesive. Corona treatment or plasma treatment can be implemented on one or both sides of each layer comprising the release resin. In the case where the substrate has the multilayer structure, the layer comprising the release resin is preferably configured on the antistatic layer side. In the case where the substrate has the multilayer structure, the surface of the antistatic layer side of the layer comprising the release resin configured on the antistatic layer side is preferably corona treated or plasma treated.

[0037] The surface energy of the surface in contact with the antistatic layer of the substrate is preferably 35~70mN / m, more preferably 35~65mN / m, further preferably 40~60mN / m. If the surface energy of the surface in contact with the antistatic layer of the substrate is above the above-mentioned lower limit, the antistatic layer coating solution described later can be evenly coated, and the thickness deviation of the antistatic layer can be reduced. If the surface energy of the surface in contact with the antistatic layer of the substrate is below the above-mentioned upper limit, the surface energy can be easily reached by corona treatment or plasma treatment. The surface energy of the surface of the substrate in contact with the antistatic layer can be adjusted by the material of the substrate constituting the surface, surface treatment, and the like.

[0038] From the viewpoint of the adhesion of the substrate and the antistatic layer, the surface energy of the surface of the substrate in contact with the antistatic layer is preferably above 20mN / m, more preferably above 30mN / m, and particularly preferably above 35mN / m. The upper limit of the surface energy is not particularly limited and can be below 80mN / m. The surface energy was determined by a surface energy evaluation method using a wetting index reagent in accordance with ISO8296:2003.

[0039] More specifically, the surface energy is obtained by the following method. Place the test piece on a horizontal platform and spread the test mixture with a cotton swab. The test mixture quickly spreads to at least 6cm 2 The area above. The amount of the test mixed liquid is such that a thin layer is formed without forming lumps. Observe the liquid film of the test mixed liquid in a bright place, and determine the surface energy of the liquid film after 2 seconds. The situation where the liquid film is not damaged and maintains the state when applied is judged as wetting. In the case where it is judged to be wetting, the surface energy of the mixed liquid with high surface tension is further determined. In the case where it is judged to be non-wetting, the surface energy of the mixed liquid with low surface tension is determined. Repeat this operation to select a mixed liquid that can accurately wet the surface of the test piece within 2 seconds. The operation of selecting a mixed liquid that can wet the surface of the test piece within 2 seconds is performed at least 3 times. The surface tension of the mixed liquid thus selected is the surface energy of the membrane.

[0040] (Antistatic layer) The antistatic layer is not particularly limited as long as it is a layer with antistatic function. The antistatic layer is arranged on the substrate adjacent to the substrate. The surface of the substrate can be modified by any treatment. In this case, the modified surface is not used as the surface property of the substrate, and can be regarded as the "substrate" of the present invention.

[0041] The antistatic layer may contain an antistatic agent. Examples of the antistatic agent include ionic liquids, conductive polymers, and conductive fillers. The antistatic agent may be used alone or in combination of two or more.

[0042] The ionic liquid may, for example, be an onium compound such as pyridinium or imidazolium, or a fluorine compound. Conductive polymers are polymers in which electrons move and diffuse along the polymer skeleton. Examples of conductive polymers include polyaniline polymers, polyacetylene polymers, polyparaphenylene polymers, polypyrrole polymers, polythiophene polymers, and polyvinylcarbazole polymers. As the conductive filler, there can be mentioned metal ion conductive salts, metal-based fillers, metal oxide-based fillers, metal-coated fillers, metal oxide-coated fillers, conductive carbon, and conductive carbon nanotubes. As the metal ion conductive salt, a lithium salt compound or the like may be mentioned. Examples of the metal oxide in the metal oxide filler and the metal oxide coated filler include tin oxide, tin-doped indium oxide, antimony-doped tin oxide, phosphorus-doped tin oxide, zinc antimonate, and antimony oxide.

[0043] The antistatic agent is preferably an antistatic agent with excellent conductivity, and more preferably at least one selected from a conductive polymer and a conductive filler. The conductive polymer or conductive filler is generally highly hydrophilic and is used in the form of a dispersed coating liquid containing water as a main component.

[0044] The antistatic agent is preferably dispersed in the binder resin. That is, the antistatic layer is preferably a layer in which the antistatic agent is dispersed in the binder resin. As the binder resin, a heat-resistant binder resin is preferred. For example, when the present laminate is used in a sealing step of a semiconductor element, it is preferred that the laminate has heat resistance at about 180°C. From the viewpoint of excellent heat resistance, the binder resin preferably includes at least one selected from (meth) acrylic resin, silicone resin, polyurethane resin, polyester resin, polyamide resin, vinyl acetate resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, trifluorochloroethylene-vinyl alcohol copolymer and tetrafluoroethylene-vinyl alcohol copolymer. Wherein, from the viewpoint of excellent mechanical strength, it is preferably composed of at least one (such as only (meth) acrylic resin) selected from (meth) acrylic resin, silicone resin, polyurethane resin, polyester resin, polyamide resin, vinyl acetate resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, trifluorochloroethylene-vinyl alcohol copolymer and tetrafluoroethylene-vinyl alcohol copolymer. In addition, from the viewpoint of excellent heat resistance and dispersibility of antistatic agent, it is preferably selected from at least one of polyester resin and (meth) acrylic resin. In the antistatic layer, the binder resin may be cross-linked. If the binder resin is cross-linked, it has better strength, heat resistance, and solvent resistance than when it is not cross-linked.

[0045] In one embodiment, from the viewpoint of solvent resistance, the antistatic layer preferably comprises a carboxyl-containing (meth) acrylic polymer and a reaction solid selected from at least one of a difunctional or higher aziridine compound (hereinafter also referred to as "polyfunctional aziridine compound") and a difunctional or higher epoxy compound (hereinafter also referred to as "polyfunctional epoxy compound") as a binder resin. In this case, the carboxyl-containing (meth) acrylic polymer reacts with at least one selected from a polyfunctional aziridine compound and a polyfunctional epoxy compound to crosslink and form a reaction solid. The antistatic layer can be a carboxyl-containing (meth) acrylic polymer and a reaction solid selected from at least one of a polyfunctional aziridine compound and a polyfunctional epoxy compound and other components.

[0046] The ratio of the units derived from the (meth)acrylic acid monomer to the entire (meth)acrylic acid polymer is not particularly limited, but is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more.

[0047] The carboxyl group of the carboxyl group-containing (meth)acrylic polymer is a crosslinkable functional group that reacts with an aziridine group in a polyfunctional aziridine compound or an epoxy group in a polyfunctional epoxy compound. The acid value of the carboxyl-containing (meth) acrylic polymer is preferably 1 to 80 mgKOH / g, more preferably 1 to 40 mgKOH / g, further preferably 1 to 30 mgKOH / g, and particularly preferably 5 to 30 mgKOH / g. The acid value of the carboxyl-containing (meth) acrylic polymer is an indicator of the ease of forming crosslinks when reacting with a polyfunctional aziridine compound or a polyfunctional epoxy compound. If the acid value is below the above upper limit, the stretchability of the antistatic layer is excellent. If the acid value is above the above lower limit, the adhesion of the antistatic layer is excellent. When the antistatic layer uses a plurality of (meth)acrylic polymers, the above range is a preferred range of the acid value of the plurality of (meth)acrylic polymers as a whole. The acid value of the (meth)acrylic acid polymer is measured according to the method specified in JIS K0070:1992.

[0048] In the carboxyl group-containing (meth)acrylic polymer, the carboxyl group may be present in the side group, at the main chain terminal, or in both the side chain and the main chain. From the viewpoint of easy adjustment of the carboxyl group content, it is preferred that the carboxyl group be present at least in the side group.

[0049] As the carboxyl group-containing (meth)acrylic polymer having a carboxyl group as a pendant, there may be mentioned a (meth)acrylic polymer having a unit based on a carboxyl group-containing monomer. Examples of carboxyl-containing monomers include carboxyl-containing (meth) acrylic acid monomers. Examples of carboxyl-containing (meth) acrylic acid monomers include carboxyl-containing (meth) acrylic acid esters and (meth) acrylic acid. Examples of carboxyl-containing (meth) acrylic acid esters include ω-carboxyl-polycaprolactone mono(meth) acrylate and mono-2-((meth) acryloyloxy) ethyl succinic acid. These monomers may be used alone or in combination of two or more.

[0050] The carboxyl group-containing (meth)acrylic polymer may be composed only of units based on a carboxyl group-containing monomer, or may further have units based on a monomer other than the carboxyl group-containing monomer. As a monomer other than a carboxyl group-containing monomer, a (meth)acrylate which does not contain a hydroxyl group and a carboxyl group, a (meth)acrylate containing a hydroxyl group, etc. These monomers may be used individually by 1 type, or may use 2 or more types together.

[0051] Examples of the (meth)acrylates containing no hydroxyl group or carboxyl group include alkyl (meth)acrylates, cyclohexyl (meth)acrylates, phenyl (meth)acrylates, toluene (meth)acrylates, benzyl (meth)acrylates, 2-methoxyethyl (meth)acrylates, 3-methoxybutyl (meth)acrylates, glycidyl (meth)acrylates, 2-aminoethyl (meth)acrylates, 3-(methacryloyloxypropyl)trimethoxysilane, trifluoromethyl methyl (meth)acrylates, and trifluoromethyl methyl (meth)acrylates. 2-perfluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, and 2-perfluorohexadecylethyl (meth)acrylate.

[0052] As the alkyl (meth)acrylate, a compound having an alkyl group with 1 to 12 carbon atoms is preferred, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.

[0053] Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate and 2-acryloyloxyethyl-2-hydroxyethyl-phthalic acid.

[0054] The mass average molecular weight (hereinafter also referred to as "Mw") of the carboxyl-containing (meth) acrylic polymer is preferably 10,000 to 1,000,000, more preferably 50,000 to 800,000, and further preferably 100,000 to 600,000. If Mw is above the above lower limit, the strength of the antistatic layer is excellent. If Mw is below the above upper limit, the stretchability of the antistatic layer is excellent. The Mw of the carboxyl group-containing (meth)acrylic polymer is a polystyrene-equivalent value obtained by measuring by gel permeation chromatography using a calibration curve prepared using a standard polystyrene sample with a known molecular weight.

[0055] The polyfunctional aziridine compound is a compound having two or more aziridine groups in one molecule. From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the number of aziridine groups in the polyfunctional aziridine compound is preferably 6 or less, particularly preferably 3 or less. Examples of the polyfunctional aziridine compound include 2,2-dihydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], 4,4-bis(ethyleneiminocarbonylamino)diphenylmethane, and trimethylolpropane-tris(β-aziridinyl)propionate. The polyfunctional aziridine compound may be used alone or in combination of two or more.

[0056] Commercially available polyfunctional aziridine compounds may be used, and examples of commercially available products include ARACOAT CL910 (trade name) manufactured by Arakawa Chemical Industries, Ltd., Chemitite (registered trademark) DZ-22E (trade name) manufactured by Nippon Shokubai Co., Ltd., and Chemitite (registered trademark) PZ-33 (trade name) manufactured by Nippon Shokubai Co., Ltd.

[0057] From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the aziridine equivalent of the polyfunctional aziridine compound is preferably above 50 g / eq, more preferably above 75 g / eq, and further preferably above 100 g / eq. From the viewpoint of improving the strength of the antistatic layer, the aziridine equivalent of the polyfunctional aziridine compound is preferably below 300 g / eq, more preferably below 250 g / eq. From this viewpoint, the aziridine equivalent of the polyfunctional aziridine compound is preferably 75 to 250 g / eq, more preferably 100 to 200 g / eq.

[0058] The polyfunctional epoxy compound is a compound having two or more epoxy groups in one molecule. From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the number of epoxy groups in the polyfunctional epoxy compound is preferably 6 or less, particularly preferably 3 or less. Examples of the polyfunctional epoxy compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, resorcinol diglycidyl ether, glycerol polyglycidyl ether, etc. The epoxy compound may be used alone or in combination of two or more.

[0059] The polyfunctional epoxy compound may be a commercially available product, and examples of the commercially available products include TETRAD-X (trade name) and TETRAD-C (trade name) manufactured by Mitsubishi Gas Chemical Co., Ltd., and Denacol (registered trademark) EX-201 (trade name) and Denacol (registered trademark) EX-313 (trade name) manufactured by Nagase ChemteX Co., Ltd.

[0060] From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the epoxy equivalent of the multifunctional epoxy compound is preferably above 30 g / eq, more preferably above 50 g / eq, and further preferably above 90 g / eq. From the viewpoint of improving the strength of the antistatic layer, the epoxy equivalent of the multifunctional epoxy compound is preferably below 300 g / eq, more preferably below 200 g / eq, further preferably below 150 g / eq, and particularly preferably below 120 g / eq. From this viewpoint, the epoxy equivalent of the multifunctional epoxy compound is preferably 30 to 300 g / eq, more preferably 50 to 200 g / eq, and further preferably 90 to 120 g / eq.

[0061] Relative to the carboxyl 100 mol% of the (meth) acrylic polymer of carboxyl, the total ratio of the aziridine radicals of polyfunctional aziridine compounds and the epoxy groups of polyfunctional epoxy compounds is preferably 15~130 mol%, particularly preferably 15~60 mol%.If the total ratio of aziridine radicals and epoxy groups is below the above-mentioned upper limit, then the cross-linking density is low enough, and the excellent adhesion between the release layer and the antistatic layer.And, when the release layer is set on the antistatic layer, the excellent adhesion between the release layer and the antistatic layer.If the total ratio of aziridine radicals and epoxy groups is above the above-mentioned lower limit, then the cross-linking density is high enough, and the strength of the antistatic layer is excellent.

[0062] The antistatic layer may contain other components in addition to the antistatic agent and the binder resin. Examples of other components include lubricants, colorants, coupling agents, and the like. Examples of the lubricant include microbeads made of thermoplastic resin, fumed silica, and polytetrafluoroethylene (PTFE) fine particles. Examples of the colorant include various organic colorants and inorganic colorants, and more specifically, cobalt blue, Bengal red, phthalocyanine blue, and the like. As the coupling agent, a silane coupling agent, a titanate coupling agent, etc. may be mentioned.

[0063] From the viewpoint of sufficiently exerting the antistatic function, the content of the antistatic agent in the antistatic layer is preferably an amount such that the surface resistance value of the laminate falls within the following range. In one embodiment, in the case where the antistatic layer is a layer obtained by dispersing an antistatic agent in a binder resin, the content of the antistatic agent relative to the binder resin can be 3 to 50% by mass, or 5 to 20% by mass. If the content of the antistatic agent is above the above lower limit, the surface resistance value of the film is easily within an appropriate range. If the content of the antistatic agent is below the above upper limit, the adhesion of the antistatic layer is easily improved.

[0064] The total content of the antistatic agent and the binder resin in the antistatic layer is preferably 10% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, and may be 100% by mass, based on the total mass of the antistatic layer.

[0065] The average thickness of the antistatic layer is, for example, 100 to 20000 nm, preferably 100 to 2000 nm, preferably 100 to 1500 nm, more preferably 100 to 1000 nm. If the average thickness of the antistatic layer is above the above lower limit, then the conductivity is excellent. If the average thickness of the antistatic layer is below the upper limit of the above scope, then the production process stability represented by the appearance of the coated surface is excellent. The average thickness of the antistatic layer is measured by optical interferometry, as described in detail in the examples below.

[0066] The thickness deviation of the antistatic layer is less than 30%, preferably below 20%, more preferably below 10%. The lower limit of the thickness deviation of the antistatic layer is not particularly limited, for example, it can be 0%, and it can also be 0.1%. If the thickness deviation of the antistatic layer is below the above-mentioned upper limit, the conductivity per unit thickness of the antistatic layer is excellent. And the uneven color caused by the uneven thickness of the antistatic layer is suppressed, and the appearance of the laminate is excellent. The thickness deviation of the antistatic layer can be measured by conventional thickness determination method. Especially for thickness below 2000nm, it is preferably measured by optical interference method. In detail, the thickness deviation of the antistatic layer is obtained by the method recorded in <thickness characteristics> described in the embodiment described later. Specifically, the thickness of the antistatic layer at 5 points is measured by optical interference method at equal intervals in the width direction of the laminate. With reflection·transmission·film thickness measurement system (for example, using Filmetricss Co., Ltd. F10-RT), the refractive index is set to 1.49 to calculate the thickness of the antistatic layer. The average value of the thickness at 5 points is the average thickness of the antistatic layer. In addition, the maximum value and the minimum value of the thickness at 5 points measured are "thickness deviation at 5 points", and the thickness deviation of the antistatic layer is obtained by the following formula. Thickness deviation of antistatic layer (%) = Thickness deviation at 5 points (nm) / Average thickness (nm) × 100

[0067] (Release layer) The release layer may be disposed on the antistatic layer adjacent to the antistatic layer, or may be disposed on the antistatic layer via another layer adjacent to the antistatic layer. The material of the release layer is not particularly limited. The release layer may be a layer having adhesiveness to other members. In one embodiment, from the viewpoint of mold release of a sealing resin (e.g., epoxy compound) used for semiconductor sealing, etc., and heat resistance that can withstand the use in a transfer molding process where the mold and the sealing resin are at high temperatures, the release layer preferably comprises a reaction cured product of a hydroxyl-containing (meth) acrylate and a difunctional or higher isocyanate compound (hereinafter also referred to as a "polyfunctional isocyanate compound"). In this case, the hydroxyl-containing (meth) acrylic polymer reacts with the polyfunctional isocyanate compound and cross-links to form a reaction cured product. The release layer may also be a reaction cured product of a hydroxyl-containing (meth) acrylic polymer, a polyfunctional isocyanate compound, and other components.

[0068] The hydroxyl group of the hydroxyl-containing (meth)acrylic polymer is a crosslinking functional group that reacts with an isocyanate group in a polyfunctional isocyanate compound. The hydroxyl value of the hydroxyl-containing (meth)acrylic polymer is preferably 1 mgKOH / g or more, more preferably 29 mgKOH / g or more, and preferably 100 mgKOH / g or less. When a plurality of (meth)acrylic polymers are used in the release layer, the above range is a preferred range of the hydroxyl value of the plurality of (meth)acrylic polymers as a whole. The hydroxyl value is measured according to the method specified in JIS K0070:1992.

[0069] The hydroxyl group-containing (meth)acrylic polymer may or may not have a carboxyl group. Like the hydroxyl group, the carboxyl group is a crosslinking functional group that reacts with an isocyanate group in a polyfunctional isocyanate compound. The acid value of the hydroxyl group-containing (meth)acrylic polymer is preferably 100 mgKOH / g or less, more preferably 30 mgKOH / g or less, and may be 0 mgKOH / g.

[0070] The crosslinking functional group equivalent of the hydroxyl group-containing (meth)acrylic polymer, that is, the total equivalent of the hydroxyl group and the carboxyl group, is preferably 500 g / mol or more, more preferably 1000 g / mol or more, and preferably 2000 g / mol or less. The cross-linking functional group equivalent is equivalent to the molecular weight between cross-linking points, and is a physical property value that determines the elastic modulus after cross-linking, i.e., the elastic modulus of the reaction cured product. If the cross-linking functional group equivalent is above the above lower limit, the elastic modulus of the reaction cured product is relatively low, and the tensile property of the release layer is excellent. If the cross-linking functional group equivalent is below the above upper limit, the elastic modulus of the reaction cured product is high, and the release layer is excellent in the release property of resins, electronic components, etc. Moreover, the components of the release layer can be suppressed from migrating to resins, electronic components, etc. The crosslinking functional group equivalent of the hydroxyl-containing (meth)acrylic polymer can be determined by dividing the molecular weight of potassium hydroxide (56.1) by the sum of the hydroxyl value and the acid value of the hydroxyl-containing (meth)acrylic polymer and multiplying the result by 1,000.

[0071] In the hydroxyl-containing (meth)acrylic polymer, the hydroxyl group may be present in the side group, at the main chain terminal, or in both the side chain and the main chain. From the viewpoint of easy adjustment of the hydroxyl content, it is preferred that the hydroxyl group be present at least in the side group.

[0072] As the hydroxyl group-containing (meth)acrylic polymer having a hydroxyl group present in a side group, a copolymer having the following unit c1 and unit c2 is preferred. Unit c1: a hydroxyl group-containing (meth)acrylate unit. Unit c2: a unit other than unit c1.

[0073] As the unit c1, for example, a unit represented by the following formula 1 may be mentioned. -(CH2-CR 1 (COO-R 2 -OH))-Formula 1 Among them, R 1 is a hydrogen atom or a methyl group; R 2 is an alkylene group having 2 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or -R 3 -OCO-R 5 -COO-R 4 -. R 3 and R 4 are each independently an alkylene group having 2 to 10 carbon atoms, R 5 It is a phenylene group.

[0074] As R 1 , preferably a hydrogen atom. R 2 , R 3 , R 4 The alkylene group in the group may be linear or branched.

[0075] Specific examples of the monomer forming the unit c1 include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate, and 2-acryloyloxyethyl-2-hydroxyethyl-phthalic acid. The monomer forming the unit c1 may be used alone or in combination of two or more. As the unit c1, from the viewpoint of excellent reactivity of the hydroxyl group, R in the above formula 1 is preferably 2 The unit is an alkylene group having 2 to 10 carbon atoms. That is, the unit is preferably a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 10 carbon atoms.

[0076] The ratio of the unit c1 to the total of all units constituting the hydroxyl-containing (meth) acrylic polymer (100 mol%) is preferably 3 mol% or more, and preferably 40 mol% or less, more preferably 30 mol% or less, and further preferably 20 mol% or less. If the ratio of the unit c1 is above the lower limit, the crosslinking density brought by the polyfunctional isocyanate compound is sufficiently high, and the mold release layer has excellent mold release properties for resins and electronic components. If the ratio of the unit c1 is below the upper limit, the mold release layer has excellent adhesion.

[0077] Unit c2 is not particularly limited as long as it is copolymerizable with the monomer forming unit c1. Unit c2 may have a carboxyl group, but preferably does not have a reactive group (eg, an amino group) other than a carboxyl group that can react with an isocyanate group. The monomer to form the unit c2 may, for example, be a macromolecule containing an unsaturated double bond, a (meth)acrylate having no hydroxyl group, (meth)acrylic acid, or acrylonitrile. As the macromolecule containing an unsaturated double bond, a macromolecule having a polyoxyalkylene chain such as (meth)acrylate of polyethylene glycol monoalkyl ether may, for example, be mentioned. Examples of the (meth)acrylate not having a hydroxyl group include alkyl (meth)acrylates, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, toluene (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, 3-(methacryloxypropyl)trimethoxysilane, trifluoromethylmethyl (meth)acrylate, and (meth)acrylate. )2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate and 2-perfluorohexadecylethyl (meth)acrylate, etc.

[0078] As the alkyl (meth)acrylate, a compound having an alkyl group with 1 to 12 carbon atoms is preferred, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.

[0079] The unit c2 preferably contains at least a unit based on an alkyl (meth)acrylate. The ratio of the (meth)acrylic acid alkyl ester unit to the total of all units constituting the hydroxyl-containing (meth)acrylic acid polymer (100 mol%) is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and preferably 97 mol% or less. If the ratio of the (meth)acrylic acid alkyl ester unit is above the above lower limit, the glass transition temperature, mechanical properties, etc. derived from the structure of the (meth)acrylic acid alkyl ester are present, and the mechanical strength and adhesion of the release layer are excellent. If the ratio of the (meth)acrylic acid alkyl ester unit is below the above upper limit, the content of the hydroxyl group is sufficient, so the crosslinking density increases and a high elastic modulus can be presented.

[0080] The Mw of the hydroxyl-containing (meth)acrylic polymer is preferably 100,000 to 1,200,000, more preferably 200,000 to 1,000,000, and further preferably 200,000 to 700,000. If the Mw is above the lower limit, the mold release layer has excellent releasability to resins, electronic components, etc. If the Mw is below the upper limit, the mold release layer has excellent adhesion. The Mw of the hydroxyl-containing (meth)acrylic polymer is a polystyrene-equivalent value obtained by measuring by gel permeation chromatography using a calibration curve prepared using a standard polystyrene sample with a known molecular weight and using the calibration curve.

[0081] The glass transition temperature (Tg) of the hydroxyl-containing (meth)acrylic polymer is preferably 20° C. or lower, more preferably 0° C. or lower. When Tg is at most the upper limit value above, the release layer exhibits sufficient flexibility even at low temperatures and is not easily peeled from the substrate. The lower limit of Tg is not particularly limited, but is preferably -60°C or higher within the above-mentioned molecular weight range. Tg is the midpoint glass transition temperature measured by differential scanning calorimetry (DSC).

[0082] The polyfunctional isocyanate compound is a compound having two or more isocyanate groups in one molecule. The isocyanate group may be protected with a blocking agent. From the viewpoint of preventing the crosslinking density of the release layer from being too high and obtaining high stretchability, the number of isocyanate groups in the polyfunctional isocyanate compound is preferably 10 or less, particularly preferably 3 or less. The polyfunctional isocyanate compound is most preferably difunctional or trifunctional.

[0083] As the polyfunctional isocyanate compound, for example, hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), dimethylbiphenyl diisocyanate (TODI), isophorone diisocyanate (IPDI), xylylene diisocyanate (XDI), triphenylmethane triisocyanate and thiophosphoric acid triphenyl isocyanate. In addition, isocyanurate bodies (i.e., trimers) and biuret bodies of these polyfunctional isocyanate compounds, and reactants of these polyfunctional isocyanate compounds with polyol compounds (e.g., adducts, difunctional prepolymers, and trifunctional prepolymers, etc.). In addition, compounds in which the isocyanate groups of these polyfunctional isocyanate compounds are protected by blocking agents can also be exemplified. As blocking agents, phenols such as meta-cresol and guaiacol, benzenethiol, ethyl acetoacetate, diethyl malonate, ε-caprolactam, etc. can be exemplified.

[0084] In one embodiment, the polyfunctional isocyanate compound preferably has an isocyanurate ring from the viewpoint that the reaction cured product (ie, adhesive layer) exhibits a high elastic modulus due to the planarity of the ring structure. Examples of the polyfunctional isocyanate compound having an isocyanurate ring include an isocyanurate form of HDI (isocyanurate-type HDI), an isocyanurate form of TDI (isocyanurate-type TDI), and an isocyanurate form of MDI (isocyanurate-type MDI).

[0085] The ratio of the isocyanate group of the polyfunctional isocyanate compound to 100 mol% of the hydroxyl group of the (meth) acrylic polymer containing hydroxyl group is preferably 20 to 115 mol%, more preferably 25 to 99 mol%, and particularly preferably 20 to 70 mol%. If the ratio of the isocyanate group is below the above upper limit, the crosslinking density is sufficiently low, and the adhesion between the release layer and the antistatic layer is excellent. If the ratio of the isocyanate group is above the above lower limit, the crosslinking density is sufficiently high, and the release layer is excellent in the releasability of the resin and electronic components.

[0086] In the release layer, the content of the reaction cured product of the hydroxyl-containing (meth)acrylic polymer and the polyfunctional isocyanate compound is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more based on the total mass of the release layer.

[0087] The release layer may contain other components in addition to the above-mentioned reaction cured product. Examples of other components include crosslinking catalysts (such as amines, metal compounds, and acids), reinforcing fillers, coloring dyes, pigments, and antistatic agents.

[0088] The crosslinking catalyst may be any substance that catalyzes the reaction (urethanization reaction) of the hydroxyl-containing (meth) acrylic copolymer and the polyfunctional isocyanate compound, and a conventional urethanization reaction catalyst may be used. Examples of the crosslinking catalyst include amine compounds such as tertiary amines, organotin compounds, organolead compounds, and organozinc compounds. Examples of the tertiary amine include trialkylamines, N,N,N',N'-tetraalkyldiamines, N,N-dialkylaminoalcohols, triethylenediamine, morpholine derivatives, and piperazine derivatives. Examples of the organotin compound include dialkyltin oxides, fatty acid salts of dialkyltins, and fatty acid salts of stannous (Japanese: first tin). As the crosslinking catalyst, an organic tin compound is preferred, and dioctyltin oxide, dioctyltin dilaurate, dibutyltin laurate, and dibutyltin dilaurate are more preferred. In addition, a dialkyltin acetylacetonate tin complex catalyst having a structure in which one atom of dialkyltin and two molecules of acetylacetone are coordinated and synthesized by reacting a dialkyltin ester with acetylacetone in a solvent may also be used. The amount of the crosslinking catalyst used is preferably 0.01 to 0.5 parts by mass based on 100 parts by mass of the hydroxyl-containing (meth)acrylic polymer.

[0089] The thickness of the release layer is preferably 50 nm or more, more preferably 100 nm or more, and preferably 2000 nm or less, more preferably 1500 nm or less, and further preferably 1000 nm or less. If the thickness of the release layer is above the above lower limit, the demoulding property is excellent. If the thickness of the release layer is below the above upper limit, the function of the antistatic layer is fully presented, and the surface resistance value of the release layer side of the laminate becomes low. The thickness of the release layer is measured in the same manner as the average thickness of the antistatic layer. Alternatively, it can be measured in the same manner as the substrate. The thickness can also be measured by wiping the release layer after coating it on the substrate while dissolving it with a solvent that dissolves the release layer, and then measuring the thickness based on the weight difference.

[0090] (Other layers) This laminate may or may not have other layers other than the substrate, antistatic layer and release layer. As other layers, gas barrier layer, coloring layer etc. may be exemplified. These layers may be used alone or in combination of two or more.

[0091] (Method for producing the present laminate) The present laminate is produced, for example, by a method of coating an antistatic layer coating liquid on one surface of a substrate to form an antistatic layer. The surface of the substrate on which the antistatic layer coating liquid is applied, that is, the surface in contact with the antistatic layer, has a surface energy of 35 to 70 mN / m. The antistatic layer coating liquid comprises water, a water-miscible organic solvent and an antistatic agent dispersible in water. The content of water is 50.0 to 99.9% by mass relative to the total amount of the antistatic layer coating liquid. The content of the water-miscible organic solvent is 14.0 to 30.0% by mass relative to the total amount of the antistatic layer coating liquid. The surface tension of the antistatic layer coating liquid is below 34 mN / m. By using the antistatic layer coating liquid, an antistatic layer having a thickness deviation less than 30% can be formed. For the antistatic layer coating liquid, detailed description will be given later.

[0092] Before the antistatic layer coating liquid is applied, the surface of the substrate to be coated with the antistatic layer coating liquid may be subjected to a surface treatment. The substrate to which the surface treatment is applied (hereinafter also referred to as "treated substrate") can be purchased commercially or manufactured by a known manufacturing method. The treated substrate can be manufactured, for example, by forming a molding material containing a resin into a film by a known molding method (such as extrusion molding or blow molding, etc.). For example, in the extrusion molding method, the molding material is melt-kneaded in an extruder, extruded into a film from a die head installed on the extruder and cooled, thereby obtaining the treated substrate. The molding material may contain additives, etc.

[0093] The surface treatment may be the same as the above-mentioned surface treatment, preferably a hydrophilic treatment, more preferably a corona treatment or a plasma treatment. From the viewpoint of industrial productivity, the corona treatment or plasma treatment is preferably performed continuously from the production process of the substrate to be treated.

[0094] The corona treatment and the plasma treatment can be performed by known methods, respectively. For example, a voltage may be applied between a grounded conveying roller and electrodes spaced apart to generate corona discharge, and a long substrate to be treated may be conveyed by the conveying roller and passed under the corona discharge, thereby subjecting the surface of the substrate on the electrode side to corona treatment. The distance between the electrode and the conveying roller is, for example, 0.1 to 10 mm. The width of the electrode (in other words, the length of the electrode in the direction perpendicular to the film conveying direction) is preferably, for example, 1 cm or more wider than the film width, and is preferably not more than the film width + 1 m from the viewpoint of efficiency. The width of the substrate to be processed is, for example, 0.1 to 3 m. The conveying speed of the substrate to be processed is, for example, 0.1 to 50 m / min. The electric power of the corona treatment is, for example, 0.1 to 50 kW.

[0095] <Antistatic layer coating liquid> By making the antistatic layer coating liquid contain a water-miscible organic solvent, the surface tension of the antistatic layer coating liquid can be reduced compared with the case where only water is contained as a liquid medium. The water-miscible organic solvent refers to an organic solvent that is miscible with water. As the water-miscible organic solvent, any organic solvent that can be uniformly miscible with water can be used, for example: alcohols such as methanol, ethanol, isopropanol (hereinafter also referred to as "IPA") and butanol; ketones such as acetone; tetrahydrofuran. The water-miscible organic solvent can be used alone or in combination of two or more. Among them, alcohols are preferred, and IPA is particularly preferred from the viewpoint of excellent compatibility with water.

[0096] As the antistatic agent dispersible in water, the above-mentioned ones may be mentioned. The antistatic layer coating liquid may contain a binder resin. As the binder resin, the above-mentioned binder resins may be mentioned, and a carboxyl group-containing (meth)acrylic polymer is preferred. The antistatic layer coating solution may also include a curing agent that crosslinks the binder resin. As a curing agent, a curing agent corresponding to the binder resin may be used. In the case where the binder resin is a carboxylic (meth) acrylic polymer, it is preferably selected from at least one of the above-mentioned polyfunctional aziridine compounds and polyfunctional epoxy compounds. As a curing agent, it may also be a carbodiimide. The antistatic layer coating liquid may further contain other additives.

[0097] The content of water is 50.0 to 99.9% by mass relative to the total amount of the antistatic layer coating solution, preferably 60.0 to 99.9% by mass, more preferably 70.0 to 95.0% by mass, and further preferably 70.0 to 86.0% by mass. If the content of water is above the above lower limit, the antistatic agent is well dispersed, and the thickness deviation of the antistatic layer decreases. If the content of water is below the above upper limit, a sufficient amount of water-miscible organic solvent can be included.

[0098] The content of the water-miscible organic solvent is 14.0 to 30.0 mass % relative to the total amount of the antistatic layer coating solution, preferably 14.0 to 25.0 mass %, and more preferably 18.0 to 25.0 mass %. If the content of the water-miscible organic solvent is above the above lower limit, the thickness deviation of the antistatic layer can be reduced. If the content of water is below the above upper limit, the surface tension of the antistatic layer coating solution decreases, and the antistatic layer coating solution can be evenly applied to the substrate, and the thickness deviation of the antistatic layer decreases. If the content of the water-miscible organic solvent is below the above upper limit, a sufficient amount of water can be included.

[0099] The ratio of water to water-miscible organic solvent is preferably 999 / 1 to 1 / 1, more preferably 999 / 1 to 1.5 / 1, further preferably 2.3 / 1 to 19 / 1, and particularly preferably 2.3 / 1 to 6.1 / 1. If the ratio is above the lower limit, it is beneficial to the dispersion of the antistatic agent and the storage stability of the coating solution is excellent. If the ratio is below the upper limit, the surface tension of the coating solution is reduced and the unevenness of the coating thickness is reduced.

[0100] The solid content concentration of the antistatic layer coating liquid is preferably 0.1 to 30.0 mass %, more preferably 1.0 to 10.0 mass %, and further preferably 1.0 to 5.0 mass % relative to the total amount of the antistatic layer coating liquid. If the solid content concentration of the antistatic layer coating liquid is above the above lower limit, the coating property is excellent. If the solid content of the antistatic layer coating liquid is below the above upper limit, it is conducive to the dispersion of the contents and the storage stability is excellent. The solid content of the antistatic layer coating liquid refers to a non-volatile component including the antistatic agent.

[0101] The surface tension of the antistatic layer coating liquid is below 34mN / m, preferably below 30mN / m, and preferably above 28mN / m. If the surface tension of the antistatic layer coating liquid is below the above-mentioned upper limit, then the antistatic layer coating liquid can be evenly coated on the substrate, and the thickness deviation of the antistatic layer decreases. From the viewpoint of coating property, the lower the better the surface tension of the antistatic layer coating liquid, but on the other hand, as the content of the water component of the solution composition increases, the property stability of the antistatic layer coating liquid can cause problems. Therefore, although not in principle, from the viewpoint of realizing the property stability of the coating liquid, the preferred surface tension is above the above-mentioned lower limit. The surface tension of the antistatic layer coating liquid can be adjusted by the type of the water-miscible organic solvent, the mass ratio of water to the water-miscible organic solvent, and the like. The surface tension of the coating liquid for the antistatic layer is measured at 23°C using a Duneuve surface tension meter. The values ​​recorded in the literature may also be used. For example, when the water-miscible organic solvent is IPA, the values ​​recorded in "Density, refractive index, viscosity and surface tension of a two-component system", Chemical Engineering, Vol. 22, No. 3, 1958 may be used.

[0102] The antistatic layer coating liquid can be prepared by mixing water, a water-miscible organic solvent, an antistatic agent, a binder resin used as necessary, a curing agent, and other additives.

[0103] <Formation of Antistatic Layer> As a coating method for the antistatic layer coating liquid, a known coating method can be applied, for example, spin coating, spray coating, injection coating, rod coating, knife coating, roll coating, blade coating, die coating, gravure coating, micro gravure coating, comma coating, slit die coating, lip coating and solution casting can be mentioned. When the antistatic layer coating liquid is continuously applied to the substrate, roll coating, gravure coating, micro gravure coating, comma coating, die coating, and the like are preferred. The coating liquid for the antistatic layer contains water as its main component. The coating liquid containing water as its main component usually has a low viscosity. When applying a coating liquid of such a property, roll coating, gravure coating and micro gravure coating are preferred. In the case of continuously coating on a substrate by gravure coating, the gravure can be rotated in the same direction as the substrate being transported, or the gravure can be rotated in the opposite direction. From the viewpoint of being able to independently set the rotation speed without relying on the substrate transport speed, the gravure reverse coating method is most preferred. On the other hand, in the case of forming a thin film of uniform thickness on a monolithic film, the spin coating method is preferred because of its simplicity.

[0104] After coating, the coating film of the antistatic layer coating liquid is dried. The drying temperature is preferably below the melting point when the material of the substrate is a crystalline polymer, and is preferably below the glass transition temperature when the material of the amorphous polymer. When the substrate is a fluororesin film, it is preferably dried below the melting point of the main material of the substrate. Moreover, the lower the temperature, the smaller the morphological change under the influence of the stress applied during the release of the forming strain of the substrate or the treatment, and a film with high dimensional accuracy can be obtained. In particular, when a fluororesin film is used for the substrate, a temperature of 25 to 120°C is preferred, and 40 to 95°C is more preferred. Drying is preferably carried out under normal pressure. After drying, the mixture may be heated to promote curing. The heating temperature is preferably 40 to 60° C. and the heating time is preferably 1 to 96 hours.

[0105] <Other Process> After forming the antistatic layer, a release layer may be formed on the surface of the antistatic layer opposite to the substrate as needed. The release layer can be formed by a known method. For example, the release layer can be formed by applying a release layer coating solution containing components for forming the release layer (e.g., the above-mentioned hydroxyl-containing (meth) acrylic polymer and polyfunctional isocyanate compound) and a liquid medium and drying. During the formation of the release layer, heating can be performed to promote curing. Heating can be performed each time each layer is formed, or after a plurality of layers are formed. Other arbitrary layers may be formed after forming the antistatic layer, before forming the release layer, or after forming the release layer.

[0106] (Characteristics of Laminated Body) The surface resistance value of the present laminate is not particularly limited and can be 10 17 Ω / □ or less, preferably 10 12 Ω / □ or less, more preferably 10 11 Ω / □ or less, more preferably 10 10 Ω / □ or less, particularly preferably 10 9 Ω / □ or less. The lower the surface resistance value, the better. There is no particular lower limit, for example, 10 3 Ω / □. The surface resistance value of the present laminate was measured in accordance with IEC60093:1980: double ring electrode method at an applied voltage of 500 V for an application time of 1 minute.

[0107] When the surface resistance value (Ω / □) of the present laminate is represented by R and the average thickness (nm) of the antistatic layer is represented by t, the value represented by 1 / (tR) is preferably within a range of 0.5×10 -4 More preferably 1.0×10 -4 More preferably, 2.0×10 -4 1 / (tR) is an index of the conductivity per unit thickness of the antistatic layer. The larger the value of 1 / (tR), the higher the conductivity per unit thickness of the antistatic layer. When the average thickness of the antistatic layer is the same, the higher the conductivity per unit thickness of the antistatic layer, the lower the surface resistance value of the laminate. The higher 1 / (tR), the better. There is no particular upper limit, for example, 300×10 -4 .

[0108] (Application of laminated body) The laminate can be used, for example, as a release film used in the process of sealing a semiconductor element with a curable resin, and can be used particularly as a release film used in the process of producing a semiconductor package having a complex shape, such as a sealed body in which a part of an electronic component is exposed from the resin.

[0109] [Method for manufacturing semiconductor package] In one embodiment, a method for manufacturing a semiconductor package includes: Disposing the laminate on the inner surface of the mold; A substrate having a semiconductor element fixed thereto is arranged in the mold having the present laminated body arranged therein; Sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and The sealing body is released from the mold.

[0110] Examples of semiconductor packages include integrated circuits in which semiconductor elements such as transistors and diodes are integrated, and light-emitting diodes having light-emitting elements. The package shape of the integrated circuit may be a shape that covers the entire integrated circuit or a shape that covers a portion of the integrated circuit (that is, a shape that exposes a portion of the integrated circuit). Specific examples include SIP (Single In-line Package), ZIP (Zigzag In-line Package), DIP (Dual In-line Package), SOJ (Small Outline J-leaded package), SON (Small Outline Non-leaded package), SOI (Small Outline I-leaded package), SOF (Small Outline F-leaded package), QFP (Quad Flat Package), QFJ (Quad Flat J-leaded package), QFN (Quad Flat Non-leaded package), QFF (Quad Flat F-leaded package), PGA (Pin Grid Array), LGA (Land Grid Array), and so on. Array: Planar Grid Array), BGA (Ball Grid Array), DTP (Dual Tape Carrier Package), QTP (Quad Tape Carrier Package), CSP (Chip Size Package / Chip Scale Package), WL-CSP (Wafer Lebel CSP), LLP (Leadless Lead Frame Package), DFN (Dual Flatpack No-leaded), MCP (Multi Chip Package), MCM (Multi ChipModule), SiP, QIP (or QUIP) (Quad In-line Package), CFP (Ceramic Flat Package), LLCC (Lead LessChip Carrier (leadless chip carrier), FOWLP (Fan Out Wafer Level Package), COB (Chip On Board), COF (Chip On Film), COG (Chip On Glass) and SVP (Surface Vertical Package), etc. As a semiconductor package, from the perspective of productivity, a package manufactured through batch packaging (Japanese: one-piece packaging) and single-chip packaging (Japanese: シンギュレーション) is preferred, and examples include integrated circuits whose sealing method is MAP (Moldied Array Packaging) or WL (Wafer Level Packaging).

[0111] As the curable resin, thermosetting resins such as epoxy resins and silicone resins are preferred, and epoxy resins are more preferred.

[0112] In one embodiment, the semiconductor package may or may not have electronic components such as a source electrode and a sealing glass in addition to the semiconductor element. In addition, a part of the semiconductor element, the source electrode, and the electronic components such as the sealing glass may be exposed from the resin.

[0113] In the method for manufacturing the semiconductor package, in addition to using the present laminate, a known manufacturing method can be used. For example, as a method for sealing the semiconductor element, a transfer molding method can be cited, and as an apparatus used in this case, a known transfer molding apparatus can be used. The manufacturing conditions can also be the same as those of the known method for manufacturing the semiconductor package. Example

[0114] The embodiments of the present disclosure are described in more detail below by way of examples, but the embodiments of the present disclosure are not limited to these examples. In the following examples, Examples 1 to 15 and Examples 31 to 33 are examples, and Examples 21 to 29 are comparative examples. "Parts" means "parts by mass".

[0115] (Evaluation method) <Thickness characteristics> The thickness of the antistatic layer was measured by optical interference at 5 points at equal intervals in the width direction of the laminate. Specifically, the thickness of the antistatic layer was calculated using the Filmetrics Co., Ltd. F10-RT reflection, transmission, and film thickness measurement system with a refractive index of 1.49. The average value of the thickness at the 5 points was the average thickness of the antistatic layer. The difference between the maximum and minimum values ​​of the thickness at the five points measured was referred to as "thickness deviation at five points", and the thickness deviation of the antistatic layer was calculated by the following formula. Thickness deviation of antistatic layer (%) = Thickness deviation at 5 points (nm) / Average thickness (nm) × 100

[0116] <Surface resistance value> At the same five measuring points as the thickness characteristic, an ultra-high resistance meter (resistance chamber R12704A manufactured by ADVANTEST) was used to apply 500 volts in accordance with JIS K 6911:1979, and the surface resistance (Ω / □) of the laminate on the side opposite to the substrate side was measured after one minute. The average of the surface resistance values ​​at the five points was the surface resistance value of the laminate. The surface resistance value (Ω / □) of the laminate is R, the average thickness (nm) of the antistatic layer is t, and the value of 1 / (tR) is calculated. The larger the value of 1 / (tR), the better the conductivity per unit thickness of the antistatic layer.

[0117] <Appearance> The refractive index of the film used as the substrate is lower than that of the antistatic layer, so if there is uneven thickness, uneven color will occur. Therefore, the laminated body prepared is pulled out for 1m, visually observed indoors under a fluorescent lamp, and evaluated according to the following benchmarks. Wherein, when the antistatic layer is formed, the coating film of the antistatic layer coating liquid cannot be formed, and no visual evaluation is performed, and it is evaluated as D. A: The display color is uniform and no uneven thickness is visible. B: There are local brightness differences such as streaks, but the color is generally fixed and no uneven thickness is observed. C: The laminated body as a whole has portions showing various colors, and thickness non-uniformity is visually observed. D: No coating film can be formed.

[0118] (Materials used) <Material of base material> ETFE-1: A copolymer of TFE / ethylene / PFBE=56.3 / 40.2 / 3.5 (molar ratio) produced in the same manner as Production Example 2 (paragraph 0118) of International Publication No. 2015 / 133630.

[0119] <Material for antistatic layer> Main agent 1: ARACOAT (registered trademark) AD610 (produced by Arakawa Chemical Industries, Ltd.). A water-based composition containing poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT-PSS), a carboxyl group-containing (meth)acrylic acid polymer, water and IPA. Solid content concentration 4.9% by mass, water 89.3% by mass, IPA 5.8% by mass. Main agent 2: PP6806 (produced by KJ Special Paper Co., Ltd.). Water-based CNT antistatic coating. Solid content concentration 10 mass%, water 90 mass%. Curing agent 1: ARACOAT CL910 (produced by Arakawa Chemical Industries, Ltd.). IPA solution of a trifunctional aziridine compound (2,2-bis(hydroxymethyl)butanol-tris[3-(1-aziridinyl)propionate]), aziridine equivalent 142 g / eq). Solid content concentration 9.5% by mass, IPA 90.5% by mass. Curing agent 2: V-02 (produced by Nisshinbo Chemical Co., Ltd.). Carbodiimide water-based resin crosslinking agent. Aqueous solution of a trifunctional aziridine compound (2,2-bis(hydroxymethyl)butanol-tris[3-(1-aziridinyl)propionate], NCN equivalent 590 g / eq). Solid content concentration 40% by mass, water 60% by mass.

[0120] <Material of release layer> Main agent 3: Nissetsu (registered trademark) KP2562 (produced by Nippon Carbide Industries, Ltd.). Diluted solution of hydroxyl-containing (meth)acrylic polymer (hydroxyl value 70 mgKOH / g, crosslinking functional group equivalent 801 g / mol), solid content 35% by mass. Curing agent 3: Nissetsu CK-157 (produced by Nippon Carbide Industries, Ltd.), solid content: 100 mass %, isocyanurate type hexamethylene diisocyanate, NCO content: 21 mass %.

[0121] (Example 1) <Preparation of base material> Using an extruder of 90mmΦ and L / D=24, ETFE-1 was formed into a film with a width of 1500mm and a thickness of 100μm by the T-die method at a temperature of 300°C. One side of the film is a mirror surface (Ra=0.05μm) and the other side is a textured surface (Ra=2.2μm). While forming, a corona treatment as a hydrophilic treatment is applied to the entire width of the mirror side. In the corona treatment, an electrode with an electrode width of 2.65m and a grounded conveying roller are configured to have a gap of about 5mm, and 5 electrodes are configured in parallel connection, and adjusted to flow an equal current. The formed film is passed through the gap at 13m / min, and corona treatment is performed at an electric power of 1800W. After the corona treatment, the surface energy of the mirror surface (corona treatment surface) side of the film is evaluated by the surface energy evaluation method using a wetting index reagent according to ISO8296:2003, and the result is 52mN / m.

[0122] <Preparation of coating solution for antistatic layer> 10 parts of the main agent 1, 1 part of the curing agent, and 1.5 parts of water and 1.5 parts of IPA as dilution media were mixed and stirred for 5 minutes to obtain an antistatic layer coating solution.

[0123] <Production of Laminated Body> The prepared substrate was placed on a film coater with a direct gravure reverse roll coating unit, and the antistatic coating liquid was applied to the mirror surface side and dried at 65°C for 1 minute to form an antistatic layer. A 150-line 45 μm gravure plate was used, and the peripheral speed ratio during coating was 130%. The above evaluation was performed on the obtained laminate. The results showed that the average thickness of the antistatic layer was 238 nm, the thickness deviation at 5 points was 21 nm, and the deviation was 9%. In addition, the appearance of the laminate was A, and the surface resistance was 20.0×10 7 , 1 / (tR) is 2.1×10 -4 .

[0124] (Examples 2 to 8, 21 to 23) In the preparation of the antistatic layer coating liquid, a laminate was obtained in the same manner as in Example 1 except that the blending amounts of the respective materials were as shown in Tables 1 and 2. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0125] (Example 9) In the preparation of the laminate, the substrate was attached to the 3-inch silicon wafer in a manner that no wrinkles appeared, the antistatic layer coating liquid was applied to the substrate by spin coating at 2000 rpm × 1 minute, and the antistatic layer was dried in a circulation oven at 65° C. for 5 minutes to form the antistatic layer. The laminate was obtained in the same manner as in Example 1. The evaluation results of the obtained laminate are shown in Table 1.

[0126] (Example 10) In the preparation of the substrate, a laminate was obtained in the same manner as in Example 1 except that a plasma treatment was performed instead of a corona treatment. The plasma treatment was performed at a high frequency voltage of 110 kHz and a discharge power density of 300 W min / m in an argon atmosphere at a pressure of 0.2 Torr. 2 After the plasma treatment, the surface energy of the mirror surface (corona treated surface) of the film was evaluated in the same manner as in Example 1 and the result was 58 mN / m. The evaluation results of the obtained laminate are shown in Table 1.

[0127] (Examples 11, 27) A laminate was obtained in the same manner as in Example 1 or Example 11 except that the power during the corona treatment was 1800 W. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0128] (Examples 12, 28) In the corona treatment, a laminate was obtained in the same manner as in Example 1 or Example 11 except that the speed through the gap of the film was 7.2 m / min and the electric power was 8500 W. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0129] (Examples 13, 29) In the corona treatment, a laminate was obtained in the same manner as in Example 1 or Example 11 except that the speed through the gap of the film was 9 m / min and the electric power was 2250 W. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0130] (Example 14) In the preparation of the antistatic layer coating liquid, a laminate was obtained in the same manner as in Example 13 except that Curing Agent 2 was used as the curing agent and 2 parts of IPA was used instead of 1.5 parts of water and 1.5 parts of IPA1.5 as the dilution solvent. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0131] (Example 15) In the preparation of the antistatic layer coating liquid, a laminate was obtained in the same manner as in Example 13 except that Main Agent 2 was used as the main agent and 3 parts of IPA were used instead of 1.5 parts of water and 1.5 parts of IPA1.5 as the dilution solvent. The evaluation results of the obtained laminate are shown in Tables 1 and 2.

[0132] (Example 24) The evaluation results of the obtained laminate are shown in Table 2, except that 10 parts of methanol was used instead of 1.5 parts of water and 1.5 parts of IPA1.5 as the dilution medium in the preparation of the antistatic layer coating liquid.

[0133] (Example 25) In the preparation of the coating liquid for the antistatic layer, 500 parts of IPA were added to replace 1.5 parts of water and 1.5 parts of IPA1.5 as the diluting medium, and then concentrated by an evaporator to 60% of the initial weight, and then toluene was added, and finally adjusted to a coating liquid having a mixed solvent composition of IPA / toluene / water=50 / 40 / 10 (mass ratio) and used, and a laminate was obtained in the same manner as in Example 1. The evaluation results of the obtained laminate are shown in Table 2.

[0134] (Example 26) When a laminate was obtained in the same manner as in Example 1 except that the corona treatment was not performed in the preparation of the substrate, the coating liquid for an antistatic layer was cracked during coating, and a coating film could not be formed.

[0135] In Tables 1 and 2, "10^7" means 10 to the seventh power, and "10^(-4)" means 10 to the -4th power. Regarding the surface tension of the antistatic layer coating liquid, for the example in which the water-miscible organic solvent is IPA, the surface tension of the mixed solution of water and IPA was calculated based on the mass ratio of water to IPA according to the description in the literature ("Density, refractive index, viscosity and surface tension of a two-component system", Chemical Engineering, Vol. 22, No. 3, 1958), and this value was used as the surface tension of the antistatic layer coating liquid. For Example 15, the surface tension value of toluene monomer was used as the surface tension of the antistatic layer coating liquid.

[0136] Table 1

[0137] Table 2

[0138] As shown in Tables 1 to 2, the surface resistance values ​​of the laminates of Examples 1 to 15 are between 26.7×10 7 Below, the antistatic performance is excellent. 1 / (tR) is 1.9×10 -4 As described above, it can be seen that the antistatic layer has excellent conductivity per unit thickness. In addition, the laminated bodies of Examples 1 to 15 also have good appearance. On the other hand, the surface resistance values ​​of the laminates of Examples 21 to 29 were between 148×10 7 The above results show that the antistatic performance is poor. The 1 / (tR) of Examples 21 to 25 and 27 to 29 in which the antistatic layer was formed was less than 0.3×10 -4 As described below, it can be seen that the conductivity per unit thickness of the antistatic layer is poor. Furthermore, the laminated bodies of Examples 21 to 25 and 27 to 29 also have poor appearance.

[0139] (Examples 31~33) The main agent 3, the curing agent 3 and the ethyl acetate are mixed in the mixing amounts shown in Table 3 to prepare a coating liquid for a release layer. The mixing amount of ethyl acetate in Examples 31 and 32 is such that the solid content of the coating liquid for the release layer is 16% by mass. The mixing amount of ethyl acetate in Example 33 is such that the solid content of the coating liquid for the release layer is 15% by mass. In Examples 1, 8 and 6, the coating liquid for the release layer is applied on the surface of the antistatic layer side of the obtained laminate with a gravure coater, respectively, and dried to form a release layer with a thickness of 0.8 μm. The coating is applied by direct gravure, using a 150#-depth 40μm roller with a width of Φ100mm×250mm as a gravure. It was dried at 100°C for 1 minute in a roller-supported drying furnace with an air volume of 19m / sec. Next, curing was performed at 40° C. for 120 hours to obtain a laminate in which the substrate, the antistatic layer, and the release layer were laminated in this order. The appearance of the obtained laminate was evaluated. The results are shown in Table 3.

[0140] Table 3

[0141] As shown in Table 3, in Examples 31 to 33, even after the release layer was formed on the antistatic layer, the excellent appearance was maintained as before the release layer was formed. Industrial Applicability

[0142] The film disclosed herein is a laminate having excellent antistatic properties. The film disclosed herein is used as a mold release film to manufacture semiconductor packages such as integrated circuits in which semiconductor elements such as transistors and diodes, source electrodes, and electronic components such as sealing glass are integrated. Explanation of symbols

[0143] 1Layer 2. Substrate 3 Antistatic layer 4 Release layer.

Claims

1. A laminate comprising a film-like substrate and an antistatic layer provided on one surface of the substrate, wherein: The surface energy of the surface of the substrate in contact with the antistatic layer is 35 to 70 mN / m, The thickness deviation of the antistatic layer is less than 30%.

2. The laminate according to claim 1, wherein The antistatic layer comprises an antistatic agent dispersible in water.

3. The laminate according to claim 2, wherein: The antistatic agent includes at least one selected from a conductive polymer and a conductive filler.

4. The laminate according to any one of claims 1 to 3, wherein The substrate comprises at least one selected from fluororesin, polymethylpentene, syndiotactic polystyrene, polycyclic olefin, silicone rubber, polyester elastomer, polybutylene terephthalate, polyethylene terephthalate and polyamide.

5. The laminate according to claim 4, wherein: The fluororesin includes at least one selected from the group consisting of ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer.

6. The laminate according to any one of claims 1 to 3, wherein The surface of the substrate in contact with the antistatic layer is subjected to corona treatment or plasma treatment. 7 . The laminate according to claim 1 , further comprising a release layer provided on a surface of the antistatic layer opposite to the substrate. 8 . The laminate according to claim 1 , which is a release film used in a step of sealing a semiconductor element with a curable resin.

9. A method for producing a laminated body comprising coating an antistatic layer coating liquid on one surface of a film-like substrate to form an antistatic layer, wherein: The surface energy of the surface of the substrate coated with the antistatic layer coating liquid is 35 to 70 mN / m, The antistatic layer coating liquid comprises water, a water-miscible organic solvent and an antistatic agent dispersible in water. The content of water is 50.0 to 99.9% by mass relative to the total amount of the antistatic layer coating liquid. The content of the water-miscible organic solvent is 14.0 to 30.0% by mass relative to the total amount of the antistatic layer coating liquid. The surface tension of the antistatic layer coating liquid is below 34 mN / m.

10. The manufacturing method according to claim 9, wherein: The water-miscible organic solvent comprises an alcohol.

11. The preparation method according to claim 10, wherein: The alcohol comprises isopropyl alcohol.

12. The production method according to any one of claims 9 to 11, wherein Before the antistatic layer coating liquid is applied, the surface of the substrate to be coated with the antistatic layer coating liquid is subjected to a corona treatment or a plasma treatment.

13. The manufacturing method according to any one of claims 9 to 11, further comprising: After forming the antistatic layer, a release layer is formed on a surface of the antistatic layer opposite to the substrate.

14. A method for manufacturing a semiconductor package, comprising: Arranging the laminate according to any one of claims 1 to 3 on the inner surface of a mold; placing a substrate having a semiconductor element fixed thereto in the mold having the stacked body arranged therein; Sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and The sealing body is demolded from the mold.

Citation Information

Patent Citations

  • Pressure detector

    JP2022139312A

  • Mold release film, method for manufacturing same, and method for manufacturing semiconductor package

    WO2015133630A1

  • Mold release film and method for manufacturing semiconductor package

    WO2016093178A1

  • Film, method for producing same, and method for producing semiconductor element using film

    WO2016125796A1

  • Mold release film and method for manufacturing semiconductor package

    CN107000268A